IMF Survey, Volume 31, Issue 05. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2002)
Almost two months after the successful launch of euro notes and coins in the 12-member euro area, IMF First Deputy Managing Director Anne Krueger says Europe now needs to tackle outstanding economic reforms more forcefully to ensure that monetary union delivers on its promise. Speaking at the Royal Institute of International Affairs in London on February 25, she refrained from commenting on the pros and cons of U.K. entry into the euro area but observed that a 'strong and prosperous European economy is essential to a strong and prosperous world economy.' Edited excerpts from Krueger s speech follow. The full text can be found on the IMFs website (www.imf.org.).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet